FOTOGRAFI URBAN LANDSCAPE DENGAN MENGGUNAKAN KAMERA LOMO - Rahmad, Cito Yasuki (Seni Media Rekam ISI Surakarta, 2010)
Urban landscape photography is not a new thing in photography. It’s similar with temple or street photography, only that the objects in focus are in urban regions. By using lomography camera the urban landscapes are caputered in special manners that new, extraordinary images appear. They are like unnatural colour, fish eye effects, and others.Keywords: Urban landscape, Lomography